Family Resilience Councelling Model in Reducing The Divorce at Religious Courts Class I-A Pontianak - Nurrahmi, Hesty; Fauziah, Fauziah; Kinanti, Kinanti (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
This research is motivated by the high divorce rate and the implementation of the mediation process in Religious Court Class I-A Pontianak in 2020-2021. The objectives of this research are to find out the factors causing the high divorce rate and how the mediation process is implemented. This research applied qualitative research methods. The research techniques used were documentation and interviews. This research reveals that: 1. The factors causing the high divorce rate in the Religious Court Class I-A Pontianak in 2020-2021 are: disputes and quarrels; economic problems; leaving their spouses; gambling; and domestic violence (KDRT), and 2. The mediation process carried out by the mediator is based on the Regulation of the Supreme Court of the Republic of Indonesia Number 1 Year of 2016, namely (a) submit a resume of the case to the mediator, the mediation process is not more than 30 days from the determination; (b) the material will be completed based on the problems experienced; (c) the mediator can invite the experts or community figures who can help resolve the problem with an agreement between the two parties and the mediator, and (d) if the mediation process is successful, the mediator is obliged to issue a peace treaty or agreement. This research provides recommendations: (a) academically, the opportunity to become a non-judge mediator can be fulfilled by alumni of the Islamic Guidance and Counselling Study Program who have taken mediator training; and (b) the mediator's ability and skills in the mediation process and the intense desire of the married couple to unite can reduce the rate of divorce.